The Relationship Between Self-Efficacy and Diet Compliance in Hypertensive Patients with Comorbidities - Setiawan, Agung Dwi; Rahayu, Sri (STIKep PPNI Jawa Barat, 2025)
Background: Hypertension is referred to as “the silent killer” because it often does not show any symptoms, so people are unaware that they have it. This condition can increase the risk of various serious diseases such as aneurysms, heart failure, metabolic syndrome which can trigger diabetes mellitus, heart disease, stroke, dementia, and an increased risk of end-stage kidney disease. Dietary compliance is very important to avoid complications of hypertension, where self-efficacy is one of the main determinants of success in maintaining dietary compliance. Objective: This study focuses on determining the relationship between self-efficacy and diet compliance in patients with hypertension and comorbidities. Methods: This study is a quantitative study with a cross-sectional design. The sampling technique used was purposive sampling, where 120 respondents with hypertension and comorbidities at Dr. Moewardi General Hospital, Surakarta, were selected. The research instruments used were a self-efficacy questionnaire and a dietary compliance questionnaire. Results: Statistical test results using SPSS and Chi-Square analysis showed a significant relationship between self-efficacy levels and diet compliance in hypertensive patients with comorbidities (P-value <0.001). Most respondents had high self-efficacy and adhered to their diet, namely 59 respondents (93.7%), while 55 respondents (96.5%) of those with low self-efficacy were non-adherent. Conclusion: This study indicates that the higher a person's self-efficacy, the higher their confidence in adhering to a diet. Therefore, interventions aimed at increasing self-efficacy can be an effective strategy for improving diet compliance